"Grafting to" approach for surface modification of AuNPs with RAFT-mediated synthesized smart polymers: Stimuli-responsive behaviors of hybrid nanoparticles. (December 2018) - Mazloomi-Rezvani, Mahsa; Salami-Kalajahi, Mehdi; Roghani-Mamaqani, Hossein
Abstract: Core-shell nanoparticles with Au core and poly((2-dimethylamino)ethyl methacrylate) (PDMAEMA) or poly( N -isopropylacrylamide) (PNIPAAm) shell were fabricated via "grafting to" approach. Reversible addition-fragmentation chain transfer (RAFT) polymerization was used to synthesize functional narrow-dispersed polymers. Thiol-capped RAFT agent was used followed by reduction of RAFT agent by NaBH4 to produce thiol-terminated polymers. Then, thiolated polymers were dissolved in medium containing colloidal Au nanoparticles (AuNPs) and polymers were grafted onto surface of AuNPs by formation of Au-S bonds. 1 H NMR was used to approve the synthesis of thiolated polymers and GPC showed that both polymers had Mn of about 15000 g/mol and dispersity of about 1.3. Fabrication of Au@polymer nanoparticles was studied by UV-vis. spectroscopy, TGA and TEM. Stimuli-responsive behavior of hybrid nanoparticles was studied by monitoring hydrodynamic diameter of samples versus temperature in aqueous media at different pH values. According to results, Au@PDMAEMA nanoparticles showed a pH-dependent thermoresponsive behavior. They showed no volume phase transition temperature (VPTT) at pH = 2 while a VPTT of 44 and 40 °C was detected at pH = 8 and 10 respectively. However, pH had no mentionable effect on thermoresponsive behavior of Au@PNIPAAm nanoparticles and they showed a VPTT of 34 °C at different pH values. Graphical abstract: Image 1 Highlights: Thiol-capped smart polymers were synthesized by RAFT polymerization. Surface of AuNPs were modified with thiolated polymers by "grafting to" method. Stimuli-responsive behavior of hybrid nanoparticles was monitored by DLS. VPTT was determined as temperature where diameter of nanoparticles decreased.